The stuff irony is made of: Translators as scholars - Feltrin-Morris, Marella (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Though barely known in the United States, Achille Campanile (1900-19 77) is considered one of Italy ’s major humorists of the twentieth century. In one of his most memorable short pieces entitled “La lettera di Ramesse” (Campanile, 1984), Campanile takes his cue from the traditional comedy of errors and gives it an original twist by setting it in ancient Egypt and creating a series of misunderstandings of a love letter written in hieroglyphics. He then tops it off by introducing a renowned scholar who, centuries later, discovers the message and publishes it in a highly acclaimed translation which, ironically, is yet another misinterpretation. This paper examines “Ramses's Letter” as a tongue-in-cheek commentary on interpretation and translation, a translation where subjectivity and desire prevail over content. It also discusses how, by rising to the empyrean of scholars, the translator becomes the target of the same irony that Campanile directs against all men of letters, and against writers in particular. Finally, since “Ramses ’s Letter” has never been available to an English-language audience, the paper features my own translation of the piece and a brief examination of the challenges I faced in approaching the ironical aspects of this text.